Financial Inclusion, Financial Technology, and the COVID-19 Pandemic: The Philippine Case - Margarita Debuque-Gonzales; Ramona Maria L. Miral; Mark Gerald C. Ruiz (Philippine Institute for Development Studies (PIDS), 2023)
The COVID-19 crisis created conditions for digital finance to accelerate financial inclusion in the Philippines. Anecdotal and survey data suggest that the pandemic has indeed spurred large gains in financial inclusion in the country, with adoption of digital finance as a strong driver. This paper empirically investigates this episode (and conjecture) by focusing on the nexus between financial inclusion, financial technology, and the pandemic. To gain better policy insight, it also chronicles and examines the evolution of the digital finance industry and the corresponding changes in financial supervision and regulation. Probit regressions using pooled Philippine microdata from the World Bank Findex Database for 2017 and 2021 show broad improvement in financial inclusion from pre-pandemic to more current times, whether through traditional or mobile accounts. Findings were generally consistent with earlier studies in that greater education, employment, and income were still associated with greater financial inclusion, though males appear to have caught up with females in formal account ownership and usage, and the poorest with the rest of society, owing to pandemic-time measures. There were exceptional increases in mobile account ownership and usage with COVID-19, however, especially for the younger, more educated, and richer groups, revealing similar distributional issues as observed with other types of accounts. The review of the digital finance landscape indicates a rather healthy interplay between suppliers of digital finance services and regulators and related agencies of government, implying a benign financial intermediation landscape so far despite rapid changes in the industry.
Keywords: 330; COVID-19; digital finance; electronic money; financial inclusion; fintech; mobile money